REDUCING ADVERSE EFFECTS FROM INTRAVENOUS N-ACETYLECYSTEINE TREATMENT OF PARACETOMOL POISONING: PRINCIPAL RESULTS OF THE SCOTTISH AND NEWCASTLE ANTEMETIC ORE_TREATMENT FOR PARACETAMOL POISONING (SNAP) RANDOMISED CONTROLLED TRIAL. Issue 10 (7th September 2013) - Gray, A; Dear, J; Thanacoody, R; Thomas, S; Eddleston, M; Sandilands, E; Coyle, J; Cooper, J; Rodriguez, A; Butcher, I; Lewis, S; Vliegenthart, A; et al.
Abstract : Objectives & Background: Paracetamol poisoning is common worldwide. Standard intravenous N-acetylcysteine (NAC) therapy is complex, and commonly associated with concentration-related adverse effects and the potential for administration errors. We aimed to determine whether adverse effect incidence could be reduced by antiemetic pre-treatment and/or a simpler and shorter intravenous N-acetylcysteine regimen. Methods: We delivered, in 3 centres, a randomised factorial trial comparing a modified 12 h (100 mg/kg over 2 h, 200 mg/kg over 10 h) with a standard 20.25 h NAC regimen (150 mg/kg 15 min, 50 mg/kg 4 h, 100 mg/kg 16 h) with and without pre-treatment with ondansetron (4 mg IV). The primary endpoint was absence of retching, vomiting or need for rescue antiemetic at 2 h; secondary endpoints included the incidence of anaphylactoid reactions, the need for medication or treatment interruption, and hepatic toxicity (ALT, INR). Results: In 217 participants, retching and vomiting were less common with ondansetron than placebo (OR 0.406, 97.5% CI 0.205–0.803, p=0.0031) and with the modified compared to the conventional acetylcysteine regimen (OR 0.260, 97.5% CI 0.130–0.518, p<0.0001). Frequency of anaphylactoid reactions was not affected by ondansetron, but less common with modified acetylcysteine; severe reactions 5/108 (4.6%) vs. 31/100 (31%) (p<0.0001). The proportion of patients with a 50% increase in ALT was not significantly different comparing conventional with modified regimens (OR 0.603, 97.5% CI 0.199–1.831), but more common with ondansetron than placebo (OR 3.295, 97.5% CI 1.013–10.723, p=0.0235). Conclusion: In patients with paracetamol poisoning requiring acetylcysteine, adverse effects were substantially reduced by ondansetron pre-treatment and by using a modified, shorter treatment regimen. Ondansetron, but not the modified regimen, increased the frequency of liver function abnormalities. If large effectiveness studies confirm the modified regimen is non-inferior to conventional then shorter and safer treatment would be possible for this common poisoning.